STRATEGI POSTER SESSION UNTUK MENINGKATKAN HASIL BELAJAR MATERI GEOMETRI PADA SISWA KELAS VIII - Atirillah (Program Studi Pendidikan Matematika, 2019)
Learning mathematics is seen as a way to practice the ability of students to think logically and systematically. Through this poster session strategy students are invited to participate in all learning processes, both mental and physical. The purpose of this study is to improve student learning outcomes by using the Poster Session strategy. This study uses classroom action research (CAR) with a qualitative approach, the subject who received the action was students of class VIIIB SMP N 1 Ende Selatan, test techniques were carried out to collect data about student learning outcomes. The level of success in terms of 3 aspects, namely the completeness of student learning assessed from the results of the test cycle I and cycle II, observation of teacher activities and student activities. Based on the results of the analysis after the implementation of the study, researchers found that the complete learning of students in the first cycle was 41% and in the second cycle was 100% so that there was an increase in student learning outcomes by 59%. The observers' observations on student activity in the first cycle of learning amounted to 57% and in the second cycle amounted to 87% so there was an increase of 30%. The observers' observations in the cycle I teacher activities were 58.92% and in the second cycle 92.85% resulting in an increase of 33.93%.